Neuroinflammation and flortaucipir PET in non‐fluent/agrammatic variant of primary progressive aphasia and/or apraxia of speech. (31st December 2021) - Pascual, Belen; Funk, Quentin; Bradbury, Kathleen; Jennings, Cassandra; Rockers, Elijah; Nakawah, Mohammad O; Yu, Meixiang; Beers, David; Faridar, Alireza; Appel, Stanley; Fujita, Masahiro; Masdeu, Joseph C
Abstract: Background: Neuroinflammation, a hallmark of frontotemporal dementia, has been sparsely studied in vivo . However, neuroinflammation is a potentially important therapeutic target and biomarkers of inflammation would be welcome. To determine the anatomical specificity of a putative biomarker for inflammation, translocator protein 18 kDa (TSPO) imaging, we used 11 C‐PBR28 PET to measure TSPO levels in patients with the non‐fluent/agrammatic variant of primary progressive aphasia (nfvPPA) and/or apraxia of speech (AOS). Methods: Sixteen patients with nfvPPP/AOS underwent PET using 11 C‐PBR28 and 18 F‐flortaucipir. All patients were PET amyloid‐negative except two, with a non‐AD flortaucipir PET. Thirty healthy controls underwent PET imaging using 11 C‐PBR28 (13 controls) or 18 F‐flortaucipir (17 controls). Patients (9/16 women, mean age 65±5.9 years) did not differ significantly in age from the controls (17/30 women, mean age 66±9.3 years). V T values for 11 C‐PBR28 were calculated with the Logan plot and a metabolite‐corrected arterial input function. For 18 F‐flortaucipir, the SUV ratio over the cerebellar gray matter was calculated for t = 80‐100 min. All images were corrected for partial volume effect. A full factorial analysis was performed on V T and SUVR values between patients and controls at the voxel‐wise level. Results: Compared to controls, patients showed increased V T and SUVR values (p < 0.001 uncorrected) in left inferior, middle and superior frontal gyri, as well as in the left putamen and pallidum. However, peak uptake of 18 F‐flortaucipir was localized in Broca's area, epicenter of the pathology, while the distribution of 11 C‐PBR28 V T was more extensive in the frontal lobe, including precentral gyrus, and other regions outside of the frontal lobe, as the supramarginal gyrus and superior temporal sulcus, as well as a small area in the posterior extent of the right inferior frontal gyrus. Conclusions: 11 C‐PBR28 and 18 F‐flortaucipir uptake patterns corresponded to anatomical areas known to be related to the specific language functions that are impaired in nfvPPA and apraxia of speech. Thus, 11 C‐PBR28 seems to be a suitable radioligand for detecting neuroinflammation in nfvPPA. Furthermore, the more extensive anatomical distribution of abnormal 11 C‐PBR28 uptake, as compared to 18 F‐flortaucipir uptake, suggests that inflammation is key to the progression of the pathologic process in nfvPPA.